Promoting Success for MBKM-Curriculum through Internship Program in Higher Education - Thohiriyah Thohiriyah; Rahma Ari Widihastuti; Marliza Arsiyana; Intan Andalas I. R. P; Nadia Sigi Prameswari (Universitas Negeri Semarang, 2023)
Under the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 3 the Year 2020 about National Standard of Higher Education and Guidance of Freedom to Learn-Independent Campus (MBKM Curriculum) Year 2020, a higher education institution has the responsibility to encourage students to have learning experiences outside the study program (Prodi) and outside home university for maximum 3 semesters. The learning experiences that the students got from outside the Study Program and home university must be transferred into academic recognition equal to 20 credits. To meet this demand, Universitas Negeri Semarang (UNNES) through MBKM Body in each faculty initiated a program that can be transferred into academic recognition equal to 12 credits namely MBKM UNNES PRIGEL Program or simply the PRIGEL program. MBKM UNNES PRIGEL is developed from Internship Program (PKL) having 12 credits-academic recognition. This paper examines how an internship program in higher education can support the implementation of the MBKM curriculum, especially in the Faculty of Languages and Arts (FBS), Universitas Negeri Semarang. A qualitative method was employed to conduct this study specifically using the PDCA method proposed by Deming in Swamidass (2000). Two main issues faced by the Faculty MBKM coordinator in UNNES are 1) designing the form of learning activities (BKP), 2) meeting the academic requirements and policy. Key strategies for supporting the policy and the development of the form of learning activity (BKP) are discussed in this paper.